Solid Biomass Uses A Mixture Of Agricultural Waste As An Alternative Fuel - Rullie Annisa; Ibnu Irawan; Rifky Yusron; Yusril Arifiyanto (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Biomass is one of the agricultural waste that can be used as an alternative fuel substitute that is converted first into a briquette, the goal is to become an environmentally friendly fuel. Corn cobs and rice straw are one of the most common types of agricultural products in East Java, therefore alternative fuel potentials that will be obtained will also be higher. Research conducted that is aimed at finding out the characteristics of solid fuel (briquettes) include: Braket’s heat values, briquette water content, briquette gray content and drop tests on briquettes using a mixture of corn cobs and rice straw. Variation of a mixture between corn cobs and rice straw of 1 kg, where 1 kg of corn cob and rice straw uses a mixture ratio of 90%: 10%, 80%: 20%, 70%: 30%and 60%: 40%by using flour adhesive kanji of 0.001 kg. Also uses two pressure variations, namely: A = 2500 kPa and B = 5000 kPa used in briquettes. The results of research from the briquette characteristics such as: the highest heat value using a 90% corn cob mixture and 10% rice straw obtained at 5546.74 Cal/gram. The most optimal water content uses an emphasis load of 5000 kPa using a 90% corn cob mixture and 10% rice straw obtained a value of 11.30%. The most optimal ash content also uses an emphasis load of 5000 kPa using a 90% corn cob mixture and 10% rice straw obtained a value of 20.58%. While the drop test value on the briquette uses a 5000 kPa pressing load using a 60% corn cob mixture and 40% rice straw obtained a value of 11.10% the large reduction of pasticles when dropped from a height.